Frequency of rehospitalization after hospitalization for suicidal ideation or suicidal behavior in patients with depression. (March 2020) - Cepeda, M. Soledad; Schuemie, Martijn; Kern, David M.; Reps, Jenna; Canuso, Carla
Highlights: A retrospective cohort study of claims data was used to identify patients with depression who were hospitalized with diagnosis of suicidal ideation or behavior, and how many of those patients were rehospitalized within 1 year. The rate of rehospitalization within a year ranged from 7.96% to 11.24%. The risk of rehospitalization after being hospitalized with diagnosis of suicidal ideation or behavior was highest during the first month. Rehospitalized patients were more likely to have an anxiety disorder, sleep disorder, or substance use disorder than those who were not rehospitalized. Abstract: This study sought to: 1. determine the frequency of rehospitalization with diagnosis of suicidal ideation or suicide attempt (SI/SA) within a year and how often patients had multiple rehospitalizations; 2. identify the time period for which the risk of rehospitalization is highest; and 3. determine the characteristics of patients with multiple rehospitalizations. We conducted a retrospective cohort study of adults with depression using 4 US health claims databases. We defined hospitalization as an inpatient or emergency room visit with codes indicating a suicide attempt or suicidal thoughts using a validated algorithm. Rates of rehospitalization with SI or SA were analyzed together and separately, including multiple re-hospitalizations with SI/SA. Across all databases 121, 065 patients were hospitalized with a diagnosis of SI/SA. Rates of rehospitalization within a year ranged from 7.96% to 11.24%. The risk of rehospitalization with SI/SA is highest during the first month. Nearly 50% of rehospitalizations occurred within 3 months after initial hospitalization. Patients with rehospitalization(s) had more anxiety disorders, sleep disorders and substance use disorders than patients without. Among patients with depression hospitalized for SI/SA, rehospitalization for SI/SA within a year is not uncommon. Risk of rehospitalization with a diagnosis of SI/SA is highest during the first month.